2020
DOI: 10.1093/aje/kwaa005
|View full text |Cite
|
Sign up to set email alerts
|

Smoking-Related Risks of Colorectal Cancer by Anatomical Subsite and Sex

Abstract: The purpose of this study was to examine whether the increased risk of colorectal cancer due to cigarette smoking differed by anatomical subsite or sex. We analyzed data from 188,052 participants aged 45–75 years (45% men) who were enrolled in the Multiethnic Cohort Study in 1993–1996. During a mean follow-up period of 16.7 years, we identified 4,879 incident cases of invasive colorectal adenocarcinoma. In multivariate Cox regression models, as compared with never smokers of the same sex, male ever smokers had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 39 publications
7
22
0
Order By: Relevance
“…With respect to colon sites, we found that in men ever smoking was associated with an increased risk of DCC, but not of PCC, a finding consistent with a recent multiethnic cohort study from North America. 36 In contrast, a meta-analysis 9 The dose-response association between smoking (for the exposure variables: pack-years of smoking and smoking intensity) and CRC observed in the present study is consistent with the pooled analyses 22 and meta-analyses. 9,21,35 Of four Asian cohort studies [10][11][12][13] (including two Japanese studies) that examined the dose-response relationship between smoking and CRC, only one study detected a progressively increasing risk associated with increasing smoking intensity or packyears.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…With respect to colon sites, we found that in men ever smoking was associated with an increased risk of DCC, but not of PCC, a finding consistent with a recent multiethnic cohort study from North America. 36 In contrast, a meta-analysis 9 The dose-response association between smoking (for the exposure variables: pack-years of smoking and smoking intensity) and CRC observed in the present study is consistent with the pooled analyses 22 and meta-analyses. 9,21,35 Of four Asian cohort studies [10][11][12][13] (including two Japanese studies) that examined the dose-response relationship between smoking and CRC, only one study detected a progressively increasing risk associated with increasing smoking intensity or packyears.…”
Section: Resultssupporting
confidence: 87%
“…Our finding of no gender difference for colon or rectal cancer is consistent with results of two studies (colon 36 or rectal cancer 36,39 ), but not with those of another study, 40 which reported a stronger association between smoking and colon cancer in women than men. With respect to subsites of the colon, in a multiethnic cohort study, 36 ever smoking was associated with a significantly increased risk of DCC in men but not in women, whereas it was associated with a significantly increased risk of PCC in women but not in men. In a Norwegian study, 40 smoking was associated with significant increase in the risk of PCC in women but not in men, whereas it showed no association with DCC risk in both men and women.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…For example, the present study revealed that the risk of second esophagus cancer was increased in CA and SRCC, and the risk of second lung and bronchus cancer was increased in CA and MA. This is likely associated with the well-established link between tobacco smoking and increased risk of CRC ( 20 , 21 ). Similarly, increased risk of second kidney cancer in CA and second corpus uteri cancer in the three subtypes of CRC could partially be associated with obesity ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%